The Role of Youth in Management of BUMdes in Kedai Durian Village, Delitua District - Mutia; Erlina; Rujiman (TALENTA Publisher, Universitas Sumatera Utara, 2021)
This research took place in Kedai Durian Village, Delitua District, Deliserdang Regency. This location was chosen based on the researcher's investigation that the BUMDes in the village were managed and run by youths whose the institution they are incorporated in Karang Taruna Citra Yodha. The business that taken by the youth of the Kedai Durian village or Karang Taruna Citra Yodha is the renting (rental), where BUMDes Kedai Durian is a business to rent tents / tratak for party. The reason this business was chosen because it was adjusted to the pontential of the region where the Kedai Durian village has a dense population. The Kedai Durian village which borders the area of ​​Medan City, indirectly also affects the condition of the village which has moved into a densely populated community. Because of the population density in Kedai Durian Village, of course has a potential to develop the rental business, where people will use a lot of these rental services.